The phenomenon of “club booths” or the production of risky parties: narrative analysis - Dragišić Labaš, Slađana M (Sociološki pregled, 2022)
This paper deals with the analysis of activities that take place in “new” booths, i.e., separate spaces in restaurants, clubs or rafts in Belgrade and other cities in Serbia that are booked and paid. We consider the behaviour of the actors (people in the booth) and of the audience (people who share the same space, but not the booths) from the viewpoint of Goffman’s dramaturgy. As is the case with all other “valuable things” in the consumer society, in the booth one can also buy and exercise “power” for a couple of hours. We learn how this plays out by following six narratives of six people (now successful abstainers from alcohol, drugs and gambling) who describe their experience of the time they still actively consumed psychoactive substances or gambled. In the booths – a special space for acting, they felt more powerful, more important, braver, more respected, richer and more successful according to the standards of consumer society. In fact, as Ritzer (2012) has it, they spent time in a “non-place” devoid of real content. Their social identities, constructed by the values of such society, outside the booth (and without the support of the audience) became uncertain and disrupted, so that the “performers” felt anxious, dissatisfied and hopeless, which was another reason for consuming PAS.